2017
DOI: 10.18632/oncotarget.18544
|View full text |Cite
|
Sign up to set email alerts
|

A pathways-based prediction model for classifying breast cancer subtypes

Abstract: Breast cancer is highly heterogeneous and is classified into four subtypes characterized by specific biological traits, treatment responses, and clinical prognoses. We performed a systemic analysis of 698 breast cancer patient samples from The Cancer Genome Atlas project database. We identified 136 breast cancer genes differentially expressed among the four subtypes. Based on unsupervised clustering analysis, these 136 core genes efficiently categorized breast cancer patients into the appropriate subtypes. Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…With the development of microarray technology and RNA sequencing technology, many studies have used gene expression profiles to classify tumors [ 25 , 26 ]. Gene expression profiles have been used to divide LUAD into subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of microarray technology and RNA sequencing technology, many studies have used gene expression profiles to classify tumors [ 25 , 26 ]. Gene expression profiles have been used to divide LUAD into subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Copy number variations (24) and single nucleotide polymorphisms (SNPs) (25) were used to train SVM classifiers for bladder, uveal cancer and breast cancer respectively. Wu et al (26) built three SVM classification models based on the identified pathways which effectively classified different breast cancer subtypes.…”
Section: Cancer Classification and Subtypingmentioning
confidence: 99%
“…EC is hormone-dependent and, like breast cancer, can express markers such as estrogen receptors (ERs), progesterone receptors (PRs) and oncoprotein c-erbB-2 (HER2) (3,4). Breast cancer can be characterized into several subgroups based on immunohistochemistry: Luminal A (ER + and/or PR + , HER2 -, low Ki67); luminal B (ER and/or PR + , HER2 -, high Ki67); non-luminal (ER -, PR -, and HER2 + ); and triple negatives (ER -, PR -, and HER2 -) (5). This classification finds clinical application in terms of prognosis and treatment personalization.…”
Section: Introductionmentioning
confidence: 99%